Phyllodes-predominant prostatic stromal sarcoma concurrent with prostate adenocarcinoma: a case report and literature review - Lian, Hongguang; Feng, Wenfeng; Zhang, Ming; Tian, Yanhua; Wu, Wenxin; Cui, Jinfeng; Wang, Yuan (Frontiers in Oncology, 2026)
Prostatic stromal sarcoma (PSS) is a rare malignant mesenchymal tumor originating from the specialized stroma of the prostate. It is a heterogeneous tumor, in which a predominantly phyllodes architecture has been documented only in isolated case reports. The co-occurrence of a phyllodes-predominant PSS and prostate adenocarcinoma (PCA) is even more exceptional. Here, we reported a case of a 52-year-old man with the chief complaint of dysuria for 2 months in 2018. Magnetic resonance imaging (MRI) revealed a mass lesion in the left lobe of the prostate. The patient underwent surgical resection, and the pathological examination revealed PSS with a phyllodes-predominant structure accompanied by PCA. We report this rare case to provide valuable clinical information for clinicians and pathologists and to improve the awareness and diagnostic level of this disease.